Peripheries. Playgrounds of Society - van Lessen, Julia; Petermann, Sandra (img journal, 2021)
Peripheries are playgrounds of society because they offer an opportunity for self-realization while designing and exploring something new. Thus, peripheries become places of social innovation, especially for people who are willing to take risks and try something new, even if they are ridiculed for it at first. They may assign less value to getting recognized by the social mainstream. Peripheries therefore offer niches to try out other ways of life and go off the beaten path, particularly when there is a need for real change.